Conscientious objections, the nature of medicine, and the need for reformability. (31st August 2021) - Kim, Eric J.; Ferguson, Kyle
Abstract: The debate over whether the medical profession should accommodate its members' conscientious objections (COs) has raged on in the bioethics literature and on legislative floors for decades. Unfortunately, participants on all sides of the debate fail to distinguish among different types of CO, a failure that obstructs the view of which cases warrant accommodation and why. In this paper, we identify one type of CO that warrants consideration for accommodation, called Nature of Medicine COs (NoMCOs). NoMCOs involve the refusal of physicians to perform actions they reasonably judge to be contrary to the nature of medicine and their professional obligations. We argue that accommodating NoMCOs can be justified based on the profession's need to preserve reformability. Importantly, this previously underdeveloped position evades some of the concerns commonly raised by opponents of CO accommodations.